Conventional vs. Innovative Protocols for the Extraction of Polysaccharides from Macroalgae; Sustainability; Vol. 14, iss. 10 - Spagnuolo D. Damiano; Di Martino A. Antonio; Zammuto V. Vincenzo; Minicante S. A. Simona Armeliъ; Spano A. Antonio; Manghisi A. Antonio; Gugliandolo C. Concetta; Morabito M. Marina; Genovese G. Giuseppa (2022, 2022)
Title screen